2017
DOI: 10.1002/2017gl073048
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of magnetospheric high‐m poloidal waves during the 22 June 2015 magnetic storm

Abstract: We report global observations of high‐m poloidal waves during the recovery phase of the 22 June 2015 magnetic storm from a constellation of widely spaced satellites of five missions including Magnetospheric Multiscale (MMS), Van Allen Probes, Time History of Events and Macroscale Interactions during Substorm (THEMIS), Cluster, and Geostationary Operational Environmental Satellites (GOES). The combined observations demonstrate the global spatial extent of storm time poloidal waves. MMS observations confirm high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…In radiation belt models, when assessing the relative contribution of ULF waves to electron dynamics, ULF wave power is typically assumed to be broadband (e.g., Ali et al, ; Brautigam & Albert, ; Brautigam et al, ; Ozeke et al, ) and the value of m is assumed to be both positive and low for all frequencies. This is in despite of evidence for discrete wave power (e.g., Claudepierre et al, ; Mann et al, ; Rae et al, ), and both high (e.g., Le et al, ) and low (e.g., Sarris et al, ), and positive (Sarris et al, ) and negative (Le et al, ) azimuthal wave numbers within the outer radiation belt. In general, these assumptions are made for three fundamental reasons.…”
Section: Introductionmentioning
confidence: 83%
“…In radiation belt models, when assessing the relative contribution of ULF waves to electron dynamics, ULF wave power is typically assumed to be broadband (e.g., Ali et al, ; Brautigam & Albert, ; Brautigam et al, ; Ozeke et al, ) and the value of m is assumed to be both positive and low for all frequencies. This is in despite of evidence for discrete wave power (e.g., Claudepierre et al, ; Mann et al, ; Rae et al, ), and both high (e.g., Le et al, ) and low (e.g., Sarris et al, ), and positive (Sarris et al, ) and negative (Le et al, ) azimuthal wave numbers within the outer radiation belt. In general, these assumptions are made for three fundamental reasons.…”
Section: Introductionmentioning
confidence: 83%
“…While standing waves observed by spacecraft usually have a second harmonic poloidal standing wave structure (Le et al, 2017;Min et al, 2017;Takahashi et al, 1985Takahashi et al, , 2018, in situ particle observation data from Van Allen Probes have confirmed the drift resonance excitation of the fundamental poloidal mode, since dE ϕ led the phase of dB r by 90°in southern hemisphere (Dai et al, 2013). While standing waves observed by spacecraft usually have a second harmonic poloidal standing wave structure (Le et al, 2017;Min et al, 2017;Takahashi et al, 1985Takahashi et al, , 2018, in situ particle observation data from Van Allen Probes have confirmed the drift resonance excitation of the fundamental poloidal mode, since dE ϕ led the phase of dB r by 90°in southern hemisphere (Dai et al, 2013).…”
Section: 1029/2018gl081573mentioning
confidence: 99%
“…ULF waves excited by internal instabilities tend to have a dominant magnetic oscillation in the radial direction and large m-number (|m| >~50), while ULF waves excited by external sources tend to have a dominant magnetic oscillation in the azimuthal direction and small m-number (|m| <~20). To estimate the m-number, several methods have been proposed: phase delay method using multiple satellites (e.g., Le et al, 2017;Takahashi et al, 1985Takahashi et al, , 2018 or ground stations (e.g., Baker et al, 2003) and the finite Larmor radius effect method (e.g., Min et al, 2017;Takahashi et al, 2018).…”
Section: Citationmentioning
confidence: 99%